Mengurai Radikalisme Agama Di Indonesia Pasca Orde Baru - Abdul Mukti Ro’uf (Ulumuna, 2007)
After the collaps of New Order regime some radical religious movements emerged. The movements that is always related to terrorism, at least by Western mass media, has made Indonesia as a battlefield either in the level of ideas or actions. In that context, Indonesian Muslims are often confused by many problems related to the emerging of radical Islamic movements. Some of the problems are: (1) epistemological problem about how to put the term “radicalism” among other terms implying similar sense, such as fundamentalism, extremism, militantism, terrorism, and jihad; (2) contextualization of radical political-religious movements in Indonesian history; (3) Islam become accused with negative stigma of radicalism. Radical Islam groups in Indonesia that emerge as a reaction of any despotic and hegemonic orders, any distortion on Islamic values, and struggle for implementing Islam completely should be responded wisely. Their way of removing violence through committing violence must be avoided by Muslim.